2017
DOI: 10.1155/2017/1289041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Free Radicals in Hemolytic Toxicity Induced by Atmospheric‐Pressure Plasma Jet

Abstract: Atmospheric-pressure plasma (APP) has received attention due to its generation of various kinds of reactive oxygen/nitrogen species (ROS/RNS). The controllability, as well as the complexity, is one of the strong points of APP in various applications. For biological applications of this novel method, the cytotoxicity should be estimated at various levels. Herein, we suggest red blood cell (RBC) as a good cell model that is simpler than nucleated cells but much more complex than other lipid model systems. Air an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Oxidative damages on membrane of red blood cells, used as a suitable and simplest model system for elucidation of redox mechanisms in this study showed that Allium sativum extracts provide greatest protection (97.7%), preventing lysis and hemolysis compared to Persea americana seed and Citrus sinensis (Figure 2). Because of the absence of nuclei, ribosomes and mitochondria coupled to lack of protein synthesis and mitochondria based oxidative reactions in mammalian RBC, the protection rate observed reflects direct interaction with the membrane (Youn et al, 2017;Zohra & Atik, 2014). Hemolysis which is therefore the result of necrosis and destruction of bilayer membrane due to deformability of its shape (Youn et al, 2017) caused by hyperglycaemia sometimes interferes with glycosylated hemoglobin (Hb1Ac) levels, very important in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative damages on membrane of red blood cells, used as a suitable and simplest model system for elucidation of redox mechanisms in this study showed that Allium sativum extracts provide greatest protection (97.7%), preventing lysis and hemolysis compared to Persea americana seed and Citrus sinensis (Figure 2). Because of the absence of nuclei, ribosomes and mitochondria coupled to lack of protein synthesis and mitochondria based oxidative reactions in mammalian RBC, the protection rate observed reflects direct interaction with the membrane (Youn et al, 2017;Zohra & Atik, 2014). Hemolysis which is therefore the result of necrosis and destruction of bilayer membrane due to deformability of its shape (Youn et al, 2017) caused by hyperglycaemia sometimes interferes with glycosylated hemoglobin (Hb1Ac) levels, very important in the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the absence of nuclei, ribosomes and mitochondria coupled to lack of protein synthesis and mitochondria based oxidative reactions in mammalian RBC, the protection rate observed reflects direct interaction with the membrane (Youn et al, 2017;Zohra & Atik, 2014). Hemolysis which is therefore the result of necrosis and destruction of bilayer membrane due to deformability of its shape (Youn et al, 2017) caused by hyperglycaemia sometimes interferes with glycosylated hemoglobin (Hb1Ac) levels, very important in the diagnosis. Allium sativum protects cell membranes, preventing alteration of lipids and proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reactive species are produced by irradiation of cold atmospheric pressure plasma jet (CAPPJ) to water. (15)(16)(17)(18) However, because there are many parameters that affect CAPPJ properties, such as the content of carrier gas, the flow rate of carrier gas, irradiation time, and irradiation distance, it is important to reveal the effects of each parameter in detail for practical applications of CAPPJ to biological samples. Here, we used CAPPJ with helium as a carrier gas and examined the effect of the distance between the plasma jet nozzle and the water surface of the sample on the generation of reactive species in the solution.…”
mentioning
confidence: 99%
“…Furthermore, Shi et al reported that CAP treatment against cancer cells induces enriched p53 pathway in SCC-15 cells [ 14 ]. Despite these advantages of CAP treatment, some drawbacks have been reported [ 15 , 16 , 17 ]. For example, CAP treatment aroused focal mucosal erosion with superficial ulceration and necrosis with inflammatory reaction, even though these mucosal damages healed within a few days [ 15 ].…”
Section: Introductionmentioning
confidence: 99%